SECOND INTERNATIONAL VILNIUS COURSE «VACCINES AS AN INSTRUMENT TO ACHIEVE BETTER QUALITY OF LIFE» - article editorial (Педиатрическая фармакология)
Dear friends! The II International Congress "Vaccines - a means to achieve better quality of life" was held in Vilnius on April 02-03, 2008. After that meeting the leading scientists-immunologists of Europe decided to include the vaccinal questions in agenda of  Europediatrics-2008 in Istanbul and Europediatrics-2009 in Moscow as mandatory points. We want to introduce you the content of the reports made by outstanding experts in the field of vaccine prevention.